ChemInform Abstract: One‐Step Synthesis of Highly Efficient Nanocatalysts on the Supports with Hierarchical Pores Using Porous Ionic Liquid‐Water Gel. Issue 39 (23rd September 2014) - Kang, Xinchen; Zhang, Jianling; Shang, Wenting; Wu, Tianbin; Zhang, Peng; Han, Buxing; Wu, Zhonghua; Mo, Guang; Xing, Xueqing
Abstract The synthesis of the title catalysts along with their application for the aerobic oxidative esterification of benzyl alcohol and the hydrogenation of benzene to cyclohexane is described.